Juvenile Dermatomyositis (JDM) Complicated by Thrombotic Thrombocytopenic Purpura (TTP) and Purtscher's Retinopathy Responsive to Rituximab: Case Report and Literature Review - Gullapalli, Keerthi; Goldzweig, Ofra; Nanda, Kabita; Chekka, Ravi; Berry, Shanail; Bukulmez, Hulya (Frontiers in Pediatrics, 2020)
Juvenile dermatomyositis (JDM) is a multisystem vasculopathy that infrequently presents with acute complications (1). We report here the case of a 12-year-old girl with JDM who developed Thrombotic Thrombocytopenic purpura (TTP) and Purtscher's retinopathy. This is the second pediatric case of JDM with TTP and Purtscher's retinopathy in the literature. The diagnosis of JDM was based on her clinical presentation (fever, myalgia, proximal muscle weakness, characteristic skin rash and elevated muscle enzymes) (2). Despite improvement of rash, fever and weakness with corticosteroids and intravenous Immunoglobulins (IVIG), the patient developed retinopathy, thrombocytopenia, hemolytic anemia, renal failure, and pulmonary edema within 1 week of initial treatment. A clinical diagnosis of TTP and Purtscher's retinopathy was made and her ADAMTS13 activity was found to be low. Regardless of aggressive treatment with pulse steroid therapy, IVIG, plasmapheresis along with multiple infusions of Fresh Frozen plasma (FFP), her condition deteriorated. In view of her worsening condition, she received one dose of Rituximab and within 48 h, her hematological and retinal involvements improved. Rituximab was given at the same dose once weekly thereafter for 4 total doses. Her disease process was halted, and retinopathy improved significantly in 48 h and continued to gradually improve over 3 weeks of maintenance therapy with cyclosporine, methotrexate, and IVIG and then stabilized. This report documents the association of TTP and Purtscher's retinopathy with JDM, emphasizing that early recognition and prompt treatment with rituximab along with the current standard of care treatment i.e., Vincristine, corticosteroids and plasmapheresis could be of potential benefit in controlling disease activity.